2018
DOI: 10.17576/jsm-2018-4704-03
|View full text |Cite
|
Sign up to set email alerts
|

5−Aminolevulinic Acid Induces Regulation in Growth, Yield and Physio-Biochemical Characteristics of Wheat under Water Stress

Abstract: The production of wheat crop is below average in many regions of the world which is ascribed to adverse environmental conditions including drought stress. The present study was conducted to appraise the beneficial role of exogenouslyapplied 5-aminolevulinic acid (ALA) on growth, yield and some key physio-biochemical characteristics of two commercially important wheat cultivars (Shafaq-06 and Uqab-2000) under well watered [100% field capacity (FC)] and water-deficit (60 and 80% FC) conditions. Imposition of var… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(6 citation statements)
references
References 27 publications
1
5
0
Order By: Relevance
“…The osmotic stress leads to the accumulation of osmotically active solutes, soluble sugars, soluble proteins, and free proline, and, interestingly enough, the exogenous ALA application further assisted in facilitating accumulation of these solutes to heighten the OA in walnut leaves and roots (Figure 5). Especially, the further accumulation of free proline in walnut leaves and roots was consistent with the phenomena reported in wheat [21], Chinese rye grass [22] and strawberry [23] under drought stress. These demonstrate that ALA stimulates the osmotic solute production, which can attract the accumulation of compatible solutes to reinforce hydration and maintain turgor in cells [9,47].…”
Section: Discussionsupporting
confidence: 88%
See 2 more Smart Citations
“…The osmotic stress leads to the accumulation of osmotically active solutes, soluble sugars, soluble proteins, and free proline, and, interestingly enough, the exogenous ALA application further assisted in facilitating accumulation of these solutes to heighten the OA in walnut leaves and roots (Figure 5). Especially, the further accumulation of free proline in walnut leaves and roots was consistent with the phenomena reported in wheat [21], Chinese rye grass [22] and strawberry [23] under drought stress. These demonstrate that ALA stimulates the osmotic solute production, which can attract the accumulation of compatible solutes to reinforce hydration and maintain turgor in cells [9,47].…”
Section: Discussionsupporting
confidence: 88%
“…As a potential growth regulator, ALA can promote plant growth and strengthen plant tolerance to various environmental stresses, including abiotic stresses (such as drought [20,23], salinity [39] and extreme temperatures [40,41]) and biotic stresses (such as pathogen infection [42]). With regard to various crops which suffered from drought stress, their drought tolerance was all improved by applying exogenous ALA on wheat [21,43], Kentucky bluegrass [20], sunflower [25], rapeseed [44] and cucumber [17]. Although the effect of exogenous ALA has been gradually clarified over the years, the mechanism of ALA-mediated drought resistance has not been thoroughly revealed.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Under water deficit conditions, plants develop mechanisms that could help the plants in survival and improved rate of production [ 7 , 8 ]. Under deficiency of water, plants upregulate defense mechanism for their survival and get control of increased accumulation of ROS (reactive oxygen species) [ 8 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, 5-ALA and citric acid can effectively mitigate chromium stress on sunflower (Farid et al, 2020). It is reported that 5-ALA successfully mitigated the adverse effects of environmental stresses of different plants species including, chilling stress in rice (Sheteiwy et al, 2017), water stress in wheat (Akram et al, 2018), and low temperature and weak light in cucumber seedling (Anwar et al, 2020).…”
Section: Introductionmentioning
confidence: 99%